Eating competence, food consumption and health outcomes : an overview - Queiroz, Fabiana Lopes Nalon de (2022)
Eating Competence (EC) is one behavioral perspective of eating practices that has been associated with a healthy lifestyle. It emphasizes eating pleasure, self-regulation of eating, body weight satisfaction, and regular meal frequency that includes food variety without focusing on dietary guidelines. EC is composed of four components (Eating Attitude, Food Acceptance, Internal Regulation, and Contextual Skill), and its assessment is performed using the Eating Competence Satter Inventory (ecSI2.0™), developed and validated in English for an adult population. EC has been associated with diet quality and health indicators for various population groups and the development of skills that increase EC might be a strategy to improve nutritional health, and prevent obesity and other chronic diseases. In this sense, this study presents an overview of the background, concepts, features, and possible associations among EC, food consumption, and health outcomes. The high prevalence of diseases associated with food/nutrition draws attention to the necessity to broaden the view on food and its relationship with health and well-being, considering not only nutrients and food combinations but also the behavioral dimensions of eating practices. Healthy nutritional recommendations that take into account attitudes and behaviors are in accordance with the EC behavioral model. Studies on eating behavior emphasize the need to better understand attitudes towards food and eating in the general population using validated instruments. In this context, measuring EC and its association with health outcomes seems to be relevant to nutritional health. The complexity of food choices has been examined in social, behavioral, and biological sciences, representing a great challenge for applying unique and simple theoretical models. Multiple methods are required, as no single theory can fully explain food selection.